MATERNAL RISK FACTORS FOR BIRTH ASPHYXIA IN LOW-RESOURCE COMMUNITIES: SYSTEMATIC REVIEW - Porman Surtana Siahaan, Hatsari Marintan (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Asphyxia is a condition in which a subject's gas exchange is blocked, resulting to progressive hypoxia, hypercarbia, and acidosis. The severity and length of the disruption determines which of these conditions will develop first. Each year, more than four million infants pass away before reaching their first birthday. The vast majority of these fatalities take place in countries that are still developing, mainly in sub-Saharan Africa and the Asia-Pacific region. As compared to the other ASEAN countries, the infant mortality rate in Indonesia is the highest. This leads to the baby being born prematurely, unable to breathe properly, and with birth defects. Indonesia has the highest neonatal mortality rate despite a steady decline from 102,700 in 2000 to 60,986 in 2017. According to the findings of study, mothers who are young, women who have anemia, and mothers who do not receive dietary assistance are all at risk for asphyxia. During pregnancy, variables that increase the likelihood of the mother or baby experiencing asphyxia include prolonged labor, malpositions, instrument-assisted births, infections, and others. It is challenging to eradicate the risk factors that contribute to birth asphyxia in developing countries. Because of a great number of causes. According to tales from the past, traditional midwives delivered babies despite having insufficient levels of training. They investigate the limited resources and educational opportunities available in rural areas, where it was standard practice to give birth at home with untrained midwives.